Computing with mirrors. (2nd January 2022) - Chattopadhyay, Tanay
Abstract: In this article, simple models of optical computing circuits ( 1 × 4 demultiplexer (DEMUX), 4 × 1 multiplexer (MUX), Boolean logic, and half-adder (HA)) are shown with mechanically controlled plane mirrors. Photographs of the proposed computational circuits are also shown. It is very useful for the school student to understand optical logic and Boolean algebra. It also shows that, computation can be possible with simple plane mirrors placed on the table. Here mirror movements are done with hand. The principle of operation of the circuits is based on reflection of light from plane mirrors. Optical devices which are used in this activity are all low-cost materials.